2019
DOI: 10.1364/boe.11.000099
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex protein-specific microscopy with ultraviolet surface excitation

Abstract: Immunohistochemical techniques, such as immunofluorescence (IF) staining, enable microscopic imaging of local protein expression within tissue samples. Molecular profiling enabled by IF is critical to understanding pathogenesis and is often involved in complex diagnoses. A recent innovation, known as microscopy with ultraviolet surface excitation (MUSE), uses deep ultraviolet (≈280 nm) illumination to excite labels at the tissue surface, providing equivalent images without fixation, embedding, and sectioning. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…The observed increase in fluorescence intensity of QD-labelled cells is expected to apply to all sizes of commercial semiconductor QDs since all sizes of QDs have absorption spectra with broadly similar distributions [10]. Therefore, all sizes of QDs are likely to have a higher absorption efficiency at 280nm compared to longer wavelengths.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The observed increase in fluorescence intensity of QD-labelled cells is expected to apply to all sizes of commercial semiconductor QDs since all sizes of QDs have absorption spectra with broadly similar distributions [10]. Therefore, all sizes of QDs are likely to have a higher absorption efficiency at 280nm compared to longer wavelengths.…”
Section: Discussionmentioning
confidence: 96%
“…More recently, Microscopy with Ultraviolet Surface Excitation (MUSE) [6,7,8,9] has identified that 280 nm light can be applied to excite fluorescence from different conventional fluorescent dyes whilst reporting further advantages of 280 nm excitation in tissue histology such as improved image contrast due to surface-limited excitation. A further application of MUSE has identified the suitability of QDs for excitation at 280 nm and applied this to multiplexed protein-specific imaging [10]. However, this work did not provide a quantitative insight into the benefits of excitation at this lower wavelength.…”
Section: Introductionmentioning
confidence: 99%
“…4 ). Although IHC staining was proposed as a potential application in previous MUSE demonstrations, it has only been demonstrated with quantum dots conjugated to antibodies 32 . To our knowledge, this is the first demonstration of MUSE IHC imaging using fluorophore-conjugated antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…3). Although IHC staining was proposed as a potential application in previous MUSE demonstrations, it has only been demonstrated with quantum dots conjugated to antibodies 27 . To our knowledge, this is the first demonstration of MUSE IHC imaging using conventional fluorophore-conjugated antibodies.…”
Section: Discussionmentioning
confidence: 99%